2016
DOI: 10.1002/jrs.4917
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic effects and the morphology changes on the active material P3HT:PCBM used in polymer solar cells using Raman spectroscopy

Abstract: There is no consensus yet that the enhancement effects of plasmonic device are predominantly caused by plasmonic effects or induced morphology changes in the optoelectronic`materials. Herein, we present a detailed Raman characterization of a typical organic P3HT:PCBM system comprising silver nanowires (Ag NWs) with different size, which can simultaneously study the plasmonic effects and the morphology changes. The direct comparison of the Raman spectra of non-annealed and annealed samples indicates that the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…42,43 Moreover, no new peak or any peak position shift is observed in the Raman spectra of samples embedding Au NSs or Au@SiO 2 NSs. In a similar way, Yang et al 44 investigated the plasmonic effects on the molecular order of P3HT:PCBM by using Raman spectroscopy at the excitation wavelength of 633 nm. This wavelength is known to be sensitive to ordered molecules but insensitive to disordered molecules for P3HT of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Moreover, no new peak or any peak position shift is observed in the Raman spectra of samples embedding Au NSs or Au@SiO 2 NSs. In a similar way, Yang et al 44 investigated the plasmonic effects on the molecular order of P3HT:PCBM by using Raman spectroscopy at the excitation wavelength of 633 nm. This wavelength is known to be sensitive to ordered molecules but insensitive to disordered molecules for P3HT of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman mappings were obtained recording spectra from areas of 100 μm × 70 μm with 1 μm of step (three of them are shown in Fig. 7a, b, c, and d), where brighter spots indicate the higher relative intensity of the band at 1445 cm −1 , assigned to symmetric C=C stretching [23,41]. The others two bands around 1381 and 728 cm −1 are attributed to C-C intra-ring stretching and C-S-C ring skeleton deformation, respectively [23,41,42].…”
Section: Morphology Of P3ht and P3ot Ls Films Before And After Gas Exmentioning
confidence: 99%
“…To investigate how the THF gas atmosphere affects the morphology of the LS films, the molecular ordering of P3HT and P3OT was analyzed before and after gas exposure. For that, three important parameters were investigated to identify the molecular ordering of these polymers: i) peak position of C=C stretching mode (1445 cm −1 ) shifts to lower wavenumbers; ii) the relative intensity of C-C mode (1381 cm −1 ) to C=C mode (1445 cm −1 ) (I C-C /I C=C ) becomes larger; and iii) full width at half maximum (FWHM) of C=C stretching mode (1445 cm −1 ) becomes narrower [41,43]. These three parameters are presented in Table 2 for the LS films of P3HT and P3OT before and after THF gas exposure.…”
Section: Morphology Of P3ht and P3ot Ls Films Before And After Gas Exmentioning
confidence: 99%
“…Yang and co‐workers describe plasmonic effects and the morphological changes or the active material P3HT:PCBM in polymer solar cells using Raman spectroscopy. The direct comparison of the Raman spectra of non‐annealed and annealed samples indicates that the morphology of plasmonic samples has changed before annealing, and the morphology of plasmonic samples and a reference sample after annealing are not distinguishable . Yin et al reported enhanced Raman scattering based on Fabry‐Perot‐like resonance in a metal‐cladding waveguide.…”
Section: Nanomaterialsmentioning
confidence: 99%